Enzyme Histochemistry of Spleen of Pig (Sus scrofa) - Kaur, Harmanpreet; Singh, Opinder; Pathak, Devendra (International Journal of Livestock Research, 2019)
The present study was conducted on the spleen of pig to elucidate the histoenzymic distribution of phosphatases and oxidoreductases. The fresh unfixed spleen samples were immediately collected after sacrifice and were subjected to cryostat sectioning at -200C with cryostat microtome. The sections were incubated with substrates for demonstration of various enzymes. The study revealed that weak to moderate alkaline phosphatase (AKPase) activity was observed in capsule and trabeculae of the spleen. The AKPase activity was moderate to strong in lymphoid follicle. The ATPase activity was seen moderate to strong in the lymphoid follicle of spleen. Uniform weak Glucose 6-phosphate activity was observed in entire spleen and capsule. Succinic dehydrogenase (SDH) activity was moderate in capsule and lymphoid follicles. Lactic dehydrogenase activity was moderate to strong in capsule and lymphoid follicles. Malic dehydrogenase (MDH) showed weak activity in the capsule and trabeculae. Nicotinamide adenine dinucleotide phosphate diaphorase (NADPH-D) and reduced Nicotinamide adenine dinucleotide diaphorase (NADH-D) was moderate in the capsule and moderate to strong in lymphoid follicles. Nonspecific esterases (NSE) activity was moderate in capsule and trabeculae. The presence of variable activity of different enzymes in spleen was correlated with maturation of lymphocytes and development of different metabolic pathways.